Promotion of Flowering by Apple Latent Spherical Virus Vector and Virus Elimination at High Temperature Allow Accelerated Breeding of Apple and Pear - Yamagishi, Norioko; Li, Chunjiang; Yoshikawa, Nobuyuki (Frontiers in Plant Science, 2016)
Plant viral vectors are superior tools for genetic manipulation, allowing rapid induction or suppression of expression of a target gene in plants. This is a particularly effective technology for use in breeding fruit trees, which are difficult to manipulate using recombinant DNA technologies. We reported previously that if apple seed embryos (cotyledons) are infected with an Apple latent spherical virus (ALSV) vector (ALSV-AtFT/MdTFL1) concurrently expressing the Arabidopsis thaliana florigen (AtFT) gene and suppressing the expression of the apple MdTFL1-1 gene, the period prior to initial flowering (generally lasts 5–12 years) will be reduced to about 2 months. In this study, we examined whether or not ALSV vector technology can be used to promote flowering in pear, which undergoes a very long juvenile period (germination to flowering) similar to that of apple. The MdTFL1 sequence in ALSV-AtFT/MdTFL1 was replaced with a portion of the pear PcTFL1-1 gene. The resulting virus (ALSV-AtFT/PcTFL1) and ALSV-AtFT/MdTFL1 were used individually for inoculation to pear cotyledons immediately after germination in two inoculation groups. Those inoculated with ALSV-AtFT/MdTFL1 and ALSV-AtFT/PcTFL1 then initiated flower bud formation starting one to 3 months after inoculation, and subsequently exhibited continuous flowering and fruition by pollination. Conversely, Japanese pear exhibited extremely low systemic infection rates when inoculated with ALSV-AtFT/MdTFL1, and failed to exhibit any induction of flowering. We also developed a simple method for eliminating ALSV vectors from infected plants. An evaluation of the method for eliminating the ALSV vectors from infected apple and pear seedlings revealed that a 4-week high-temperature (37°C) incubation of ALSV-infected apples and pears disabled the movement of ALSV to new growing tissues. This demonstrates that only high-temperature treatment can easily eliminate ALSV from infected fruit trees. A method combining the promotion of flowering in apple and pear by ALSV vector with an ALSV elimination technique is expected to see future application as a new plant breeding technique that can significantly shorten the breeding periods of apple and pear.